2011
DOI: 10.1100/tsw.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Multiforme Stem Cells

Abstract: Glioblastoma multiforme (GBM) is an aggressive, malignant, and lethal brain tumor, resistant to all current forms of treatment. The rapidly emerging focus on cancer stem cells embodies a paradigm shift in our understanding of tumor pathogenesis, while the development of powerful genome-wide screening techniques has provided cause for optimism related to the development of more reliable therapies primarily targeting GBM stem cells (GBMSCs). There are promising mounting data on providing new molecular targets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 243 publications
1
31
0
3
Order By: Relevance
“…Some authors suggest that the autocrine and paracrine stimulation of PDGFRβ could play an essential role in glial tumorigenesis [4,31]. It was revealed that during glioma progression the PDGFRβ stimulation can induce the activation of different signaling receptors like EGFR, Notch which lead to dedifferentiation of glioma cells, and increase cell motility and malignancy of the tumor [8,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors suggest that the autocrine and paracrine stimulation of PDGFRβ could play an essential role in glial tumorigenesis [4,31]. It was revealed that during glioma progression the PDGFRβ stimulation can induce the activation of different signaling receptors like EGFR, Notch which lead to dedifferentiation of glioma cells, and increase cell motility and malignancy of the tumor [8,31].…”
Section: Discussionmentioning
confidence: 99%
“…Grade I/II astrocytomas are slow-growing tumors without aggressive features, whereas grade III and IV glio mas possess a malignant phenotype associated with high proliferative activity and vascular formation [18,19]. Glioblastoma (grade IV) is one of the most aggressive and deadly malignant brain tumors with an average survival time of 15 months after diagnosis [8,13,18,20]. Most primary glioblastomas develop de novo but some parts of diffuse astrocytomas grade II and III may progress to grade IV as secon dary glioblastomas [12,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many markers potentially specific for GSCs have been proposed such as A2B5 cell surface ganglioside epitope (A2B5) [26,27], aldehyde dehydrogenase (ALDH) [28], BMI1 polycomb ring finger oncogene (BMI1) [29,30], fucosyltransferase 4 (FUT4) (CD15) [31], Thy-1 cell surface antigen (Thy-1) (CD90) [32], prominin-1 (PROM1) (CD133) [5,6], chemokine (C-X-C motif) receptor 4 (CXCR4) [33], inhibitor of DNA binding 1 (ID1) [34], integrin α6 (ITGA6) [35], L1 cell adhesion molecule (L1CAM) [36], maternal embryonic leucine zipper kinase (MELK) [37], musashi-1 (msi1) [38], nestin (NES) [38][39][40], octamer-binding transcription factor 4 (OCT4) [41], OLIG2 [42] and SOX2 [38,[43][44][45]. Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%